Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/apt.14583
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: symptom association probability during reflux testing—what is the gain?

Abstract: Editorial: symptom association probability during reflux testing-what is the gain?Reflux monitoring is indicated for patients with suspected refractory reflux symptoms, but without convincing oesophagitis on endoscopy.1 Significantly abnormal acid exposure (ie > 6%) equates to a diagnosis of gastro-oesophageal reflux disease (GERD). 2 However that begs the question of whether or not the refractory symptoms are reflux-related. The symptom index (SI) and symptom association probability (SAP) were developed to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…22 Nevertheless, it is widely recognized that the fewer the number of symptoms reported, the less reliable the SAP becomes. 23 Thus, in our study we considered as not-reliable SAP when the symptom was reported less than 3 times during the MII-pH. Based on MII-pH results, we categorized the enrolled patients in 4 subgroups: (1) The post reflux swallow induced peristaltic wave (PSPW) was defined as an antegrade 50% drop in impedance starting in the most proximal impedance channel and reaching the most distal impedance channel, occurring within 30 seconds after a reflux event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Nevertheless, it is widely recognized that the fewer the number of symptoms reported, the less reliable the SAP becomes. 23 Thus, in our study we considered as not-reliable SAP when the symptom was reported less than 3 times during the MII-pH. Based on MII-pH results, we categorized the enrolled patients in 4 subgroups: (1) The post reflux swallow induced peristaltic wave (PSPW) was defined as an antegrade 50% drop in impedance starting in the most proximal impedance channel and reaching the most distal impedance channel, occurring within 30 seconds after a reflux event.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Nevertheless, it is widely recognized that the fewer the number of symptoms reported, the less reliable the SAP becomes. 23 Thus, in our study we considered as not-reliable SAP when the symptom was reported less than 3 times during the MII-pH. Based on MII-pH results, we categorized the enrolled patients in 4 subgroups: (1) abnormal RI (NERD); (2) normal RI and abnormal SAP (RH); (3) normal RI and normal SAP (FH); and (4) normal RI and not-reliable SAP (normal RI not otherwise specified [“normal RI-NOS”]).…”
Section: Methodsmentioning
confidence: 99%
“…17 Sin embargo, esto no responde la pregunta de si los síntomas están o no relacionados con el reflujo. 186 El IS y el SAP fueron desarrollados para responder esta pregunta. 187 Es muy importante tener en cuenta que estas métricas surgieron para la pH-metría sin monitoreo de impedancia y para los síntomas típicos de reflujo (pirosis, dolor torácico y regurgitación).…”
Section: ¿Se Recomienda El Uso De Los íNdices (Is Y Sap) En Pacientes...unclassified
“…204 A partir de esta publicación, dos editoriales cuestionaron el valor de la utilización de los índices sintomáticos para el diagnóstico de ERGE. 186,205 Posteriormente, Spechler y col. publicaron en el año 2019 un osado ensayo clínico aleatorizado, en el que eva-luaron el tratamiento médico versus el quirúrgico. Incluyeron a 78 pacientes altamente seleccionados con pirosis refractaria y SAP positiva (ERGE e hipersensibilidad al reflujo).…”
Section: ¿Se Recomienda El Uso De Los íNdices (Is Y Sap) En Pacientes...unclassified
“…A causality of the cough with confirmed reflux can be assumed if there is a high symptom association probability (SAP) of >95% with cough episodes [69]. However, not all patients performing pH-probe are able to fully record their cough episodes by manual signal input at the device [70,71]. The lower the number of reflux episodes, the more likely an overinterpretation of an apparently high SAP [72].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%